Analysis Before and After the Implementation of PSAK 72 on the Financial Performance of PT Ciputra Development Tbk in 2018-2021 - Lestari, Sri Indah; Arizah, Ainun (Amsir Accounting & Finance Journal, 2025)
This study aims to evaluate the effect of the implementation of PSAK 72 on income recognition as reflected in the performance of the financial company PT Ciputra Development Tbk in 2018-2021, one of the largest property companies in Indonesia listed on the Indonesian stock exchange. PSAK 72 came into effect on January 1, 2020, and significantly changed the company's revenue recognition method from the settlement percentage method to a recognition based on revenue transfer to customers. This study uses a comparative descriptive quantitative approach by analyzing financial ratios: Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), and Net Profit Margin (NPM) in the 2018-2021 period. The results of the study show that there is a significant change in the recognition of income from these ratios. Once PSAK 72 was implemented, revenue recognition became more conservative but provided greater transparency and assisted stakeholders in decision-making.